Developing Disaster Literacy through STEM-Ethnoscience Integration: Evidence from Primary School Contexts - Setyo Eko Atmojo; Rina Dyah Rahmawati (Jayapangus Press, 2026)
Disaster literacy is an essential competency for primary school students, particularly in disaster-prone regions; however, it is often not optimally integrated into classroom learning. This study aims to examine the effectiveness of integrating STEM (Science, Technology, Engineering, and Mathematics) with ethnoscience to enhance disaster literacy among primary school students. The research employed a quasi-experimental design involving elementary students selected through purposive sampling. Data were collected through tests, questionnaires, and observations to measure students’ knowledge, awareness, and preparedness related to disaster risk. The main statistical analyses used were the t-test and N-gain to compare disaster literacy between groups. The learning intervention integrated local wisdom (ethnoscience) into problem-oriented STEM activities relevant to students’ real-life contexts. The results showed a significant difference in disaster literacy between the experimental and control groups, with t (58) = 3.27 and p = 0.002 (p < 0.05). The experimental group demonstrated higher improvement (N-gain = 0.62; moderate category) compared to the control group (N-gain = 0.29; low category). These findings indicate that STEM-ethnoscience learning significantly improves students’ disaster literacy. This approach also provides a meaningful and culturally relevant framework for disaster education. In conclusion, the STEM-ethnoscience approach is an effective and innovative pedagogical strategy for enhancing disaster awareness and preparedness in primary education.